PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN IKAN PADA UD. IRIAN MANDIRI - SAPUTRA, IRIANSYAH; Ridwan, Ridwan (Patria Artha University, 2025)
This research aims to analyze the influence of service quality, price and location on fish purchasing decisions at UD. Irian Independent. This research uses quantitative methods with a sample size of 50 respondents. Data analysis was carried out using multiple linear regression and t test to determine the effect of each independent variable on the dependent variable. The research results show that service quality (X1) has a significant effect on purchasing decisions with a coefficient value of 0.504 and a significance value of 0.000 (p 0.05). The price variable (X2) also has a significant effect with a coefficient value of 0.407 and a significance of 0.003 (p 0.05). Meanwhile, the location variable (X3) has no significant effect on purchasing decisions with a coefficient value of 0.009 and a significance of 0.853 (p 0.05). Based on the results of this research, it can be concluded that service quality and price have a significant influence on fish purchasing decisions at UD. Irian Mandiri, while the location factor does not have a significant influence. The implication of this research is that UD. Irian Mandiri needs to improve service quality and establish a competitive pricing strategy to improve consumer purchasing decisions.